COVID-19 Anxiety and Washing Obsessive-compulsive Symptoms: Stress Coping Styles as a Mediator - Zanjani, Zahra; Jandaghian, Maryam; Alvani, Seyed R.; Ghorbani, Vajiheh; Joekar, Sanaz (Current Psychiatry Research and Reviews, 2023)
Background: The COVID-19 pandemic has significantly impacted people's psychological functioning, including how they cope with anxiety. This study aimed to assess the role of coping styles in the relationship between COVID-19 anxiety and Washing Obsessive- Compulsive Disorder (W-OCD) symptoms. Methods: A cross-sectional study was performed on 420 people living in Kashan city (Iran) from March to April, 2020. Participants were selected by the convenience sampling method due to the difficulties brought about by COVID-19 and completed the contamination subscale of the Padua Inventory, COVID-19 anxiety inventory, and coping strategies scale. Data were analyzed by structural equation modeling (SEM) using AMOS- 22. Results: The results revealed that emotion-focused, somatization and social support coping strategies were significantly associated with W-OCD symptoms. Also, there was a significant correlation between COVID-19 anxiety and the W-OCD symptoms. SEM results revealed that emotion-focused and somatization coping strategies positively mediated the relationship between COVID-19 and W-OCD symptoms. Conclusion: Emotion-focused and somatization coping strategies increase W-OCD symptoms following COVID-19 anxiety. Psychoeducation interventions addressing COVID-19's physical and psychological impacts on health, discriminating the rational and adaptive behavior and obsessive and compulsive behaviors, and restricting the information gathering from numerous sources, which may lead to increased negative emotions, might be helpful.
Keywords: structural equation modeling